15 : [ 11 - ( 7 × 5 - 9 × 9 : X : 3 ) : 8 + 2 × 4 ] × 3 = 3
15 : [ 11 - ( 35 - 81 : X : 3 ) : 8 + 8 ] × 3 = 3
15 : [ 11 - ( 35 - 81 : X : 3 ) : 8 + 8 ] = 3 : 3
15 : [ 11 - ( 35 - 81 : X : 3 ) : 8 + 8 ] = 1
11 - ( 35 - 81 : X : 3 ) : 8 + 8 = 15 : 1
11 - ( 35 - 81 : X : 3 ) : 8 + 8 = 15
11 - ( 35 - 81 : X : 3 ) : 8 = 15 - 8
11 - ( 35 - 81 : X : 3 ) : 8 = 7
( 35 - 81 : X : 3 ) : 8 = 11 - 7
( 35 - 81 : X : 3 ) : 8 = 4
35 - 81 : X : 3 = 4 × 8
35 - 81 : X : 3 = 32
81 : X : 3 = 35 - 32
81 : X : 3 = 3
81 : X = 3 × 3
81 : X = 9
X = 81 : 9
X = 9